Maternal Executive Functioning, Emotional Availability and Psychological Distress During Toddlerhood: A FinnBrain Birth Cohort Study - Nordenswan, Elisabeth; Deater-Deckard, Kirby; Karrasch, Mira; Laine, Matti; Kataja, Eeva-Leena; Holmberg, Eeva; Eskola, Eeva; Hakanen, Hetti; Karlsson, Hasse; Karlsson, Linnea; Korja, Riikka (Frontiers in Psychology, 2021)
Executive functioning (EF) is one of the building blocks in parental caregiving behavior, and contextual variables have been reported to moderate the link between EF and caregiving behavior. Although psychological distress due to various factors is prevalent during early parenthood and is negatively associated with adult EF, it is not known whether psychological distress influences the maternal EF/caregiving link. This study explored the association between maternal EF and caregiving behavior (more specifically, Emotional Availability/EA), and whether single and cumulative maternal psychological distress domains moderated the EF/EA association in a general population sample of 137 Finnish birth cohort mothers with 2.5-year-old children. EF was measured with a composite of five computerized Cogstate tasks, EA with the Emotional Availability Scales, and three psychological distress domains with self-report questionnaires (depression: EPDS, anxiety: SCL-90, insomnia: AIS). Better EF was significantly associated with more positive, sensitive caregiving, but this association was no longer significant when controlling for education level. Neither individual nor cumulative distress domains moderated the EF/EA association significantly, although the observed moderation effects were in the expected direction. These findings suggest that EF should be recognized alongside socioemotional factors as variables that are associated with parental caregiving behavior during toddlerhood. Furthermore, if the non-significant moderation results are replicated, they indicate that mothers in community samples are not at great risk for psychological distress that would compromise their capacity to utilize their EF while caring for their child. Further studies are needed to confirm these findings, as well as to examine these associations among fathers and in samples that have higher levels of chronic stressors. Studies with more diverse samples in terms of distress levels and EF performance would provide further insight into early childhood parenting and its risk factors.